PENTAGAMAVUNON-1 MENGHAMBAT SIKLUS SEL T47D TERINDUKSI CASPASE INHIBITOR Z-VAD-Fmk PADA FASE G2-M - Daâ??i, Muhammad; A.M., Supardjan; Jenie, Umar Anggara; M, Kawaichi; Meiyanto, Edy (Jurnal Farmasi Indonesia, 2011)
Previous experiment indicated Curcuminâ??s analogue Pentagamavunon-1 (2,5-bis(41-hidroxy-31,51-dimethyl)-benzilidine-cyclopentanone) has inhibitory activity on T47D cell proliferation through induction of apoptosis and cell cycle arrest at G2-M phase. This research was conducted to observe the relationship between the induction of apoptosis and inhibition of cell cycle in T47D cells induced by Pentagamavunon-1 (PGV-1). The T47D cells were treated with 2.5 PGV-1 mM; Z-VAD-Fmk 2.5 mM; (Z-VAD-Fmk 2.5 mM+PGV-1 2.5 mM). Kinetics of cell proliferation was observed with flowcytometer analysis, molecular expression was observed with Western blot methods. The results showed induction of PGV-1 and Z-VAD-Fmk stimulate the accumulation of cells in G2-M phase (39.28%), did not differ significantly with cells that Â induced by PGV-1 only (34.19%). Molecular analysis showed that treatment with (PGV-1+Z-VAD-Fmk) could prevent apoptosis through inhibition of activation of Caspase-3, increased the expression of p21 and activated Cdc-2. Overall the study showed inhibition of cell cycle at G2M phase by PGV-1 compound is not affected by the activation of caspase-3. ABSTRAK Analog kurkumin Pentagamavunon-1 Â (2,5-bis(41-hidroksi-31,51-dimetil)-benzilidinsiklo-pentanon) telah diteliti dapat menghambat proliferasi sel melalui mekanisme induksi apoptosis dan cell cycle arrest pada fase G2-M. Penelitian ini dilakukan untuk mengamati keterkaitan antara proses induksi apoptosis dan penghambatan siklus sel pada sel T47D yang diinduksi senyawa Pentagamavunon-1 (PGV-1). Sel T47D diberi perlakuan PGV-1 2,5 mM; Z-VAD-Fmk 2,5 mM dan (Z-VAD-Fmk 2,5 mM+PGV-1 2,5 mM). Kinetika proliferasi sel diamati dengan analisis flowcytometric, ekspresi molekuler diamati dengan metode Western blot. Hasil pengamatan menunjukkan induksi (PGV-1+Z-VAD-Fmk) memacu akumulasi sel pada fase G2-M (39,28%) tidak berbeda signifikan dengan sel yang hanya diinduksi PGV-1 (34,19%). Pengamatan molekuler menunjukkan perlakuan (PGV-1+Z-VAD-Fmk) mencegah terjadinya apoptosis melalui penghambatan aktivasi Caspase-3. Secara keseluruhan penelitian menunjukkan penghambatan siklus sel pada fase G2-M oleh senyawa PGV-1 tidak tergantung oleh aktivasi Caspase-3.